Socio-economic profile of duck farmers and duck management practices in Rajshahi region - Alam, MB; Uddin, ABMS; Bablu, MAZH; Kamaly, MHK; Rahaman, MM (Bangladesh Journal of Animal Science, 2013)
The present study was conducted to determine the socio-economic profiles of the duck farmers and to investigate the management practices of duck farming and to identify the problems of duck farming in two upazilas of Rajshahi district namely: Bagmara and Tanore during the period from April to May 2012 by using a pre-tested questionnaire. Socio-economic profile of the duck farmers like age, education, family size, occupation, marital status, farm size, training received, annual income and management practices particularly housing, feeding, breeding, cleaning, disposal of diseased/dead birds, vaccination program, veterinary services followed by the farmers were investigated during the research. A total of 100 duck (50 from each upazila) were selected randomly for this study. The results reveal that most of the respondent farmers were young (60%) having secondary level of education (69%). Family size of the most of the farmers (57%) were small (size 4.53 persons) and majority of the farmers (75%) were marginal (0.021-020 hectare). Most of the farmers were medium income group (57%) with mean annual income of Tk. 200500. About 42% farmers had training on farming of different duration (7 to 30 d). Highest proportion of the duck houses were made of tin-shed (74%) having necessary floor space for ducks. The data obtained illustrated that majority of the farmers (74%) used sufficient supplementary feed to their ducks. About 65% of the farmers reared Deshi ducks in their farms. Most of the farmers (70%) cleaned their farm houses regularly. About 73% farmers separated their diseased duck from healthy ones. It was also found that most of the farmers (89%) buried their dead ducks under soil. Data indicated that majority of the farmers (67%) had partial idea about duck diseases. The highest proportion of the farmers (72%) followed vaccination program strictly. About 71% farmers consulted with village doctor. Nearly 51% farmers had low level of knowledge about duck farming. In the present study 10 problems were identified out of which low price of duck meat and egg made ranked as most serious problems. If the problems are addressed properly, the duck raising could be more profitable business in Bangladesh. DOI: http://dx.doi.org/10.3329/bjas.v41i2.14124 Bang. J. Anim. Sci. 2012. 41 (2): 96-105